Electrospinning of antibacterial and anti-inflammatory Ag@hesperidin core-shell nanoparticles into nanofibers used for promoting infected wound healing. (18th February 2022) - Ren, Xiuli; Hu, Yanan; Chang, Linna; Xu, Shibo; Mei, Xifan; Chen, Zhenhua
Abstract: Bacterial infection and excessive inflammation are still the main obstacles to wound repair. Thus, antibacterial and anti-inflammation nanomaterials are always attracting for infected wound healing. In this work, ultra-uniform (∼20 nm) and colloidally stable Ag nanoparticles (Ag-Hes NPs) with core-shell structure were prepared by using hesperidin as reducing and capping agent. The obtained Ag-Hes NPs present effective antibacterial properties on both Staphylococcus aureus and Escherichia coli . Ag-Hes NPs also got high 1, 1-diphenyl-1-picrylhydrazyl scavenging capability of 69%. Under the package of polyvinyl alcohol and sodium alginate, Ag-Hes NPs were encapsulated into electro spun nanofibers to form hydrogel (Ag-Hes@H). This strategy provides a moisture environment which could enrich and release Ag-Hes NPs gradually. Cell experiments and animal wound healing investigation proved that Ag-Hes@H could promote the proliferation and migration of human umbilical vein endothelial cells and accelerate infected wound healing. Meanwhile, Ag-Hes@H significantly reduced the expression of inflammatory cytokines, including IL-6, MMP9 and TNF-α. Immunohistochemistry data further suggested that Ag-Hes@H accelerated wound closure by promoting collagen deposition and skin cell proliferation. The designed antibacterial and anti-inflammatory Ag-Hes@H has great potential for promoting infected wound healing. Graphical Abstract: